Bioderived nanostructure and their functional contribution in immobilization of cellulolytic enzymes for improving biosensing application - Tripathi M.; Singh R.; Tripathi S.C.; Srivastava N. (My University, 2025)
Cellulases fall under the biocatalyst and one of industrial enzymes which is highest in demand due to diverse and huge applications. It plays major role in cellulosic bioenergy production achieving biomass hydrolysis for sugar and energy production. Inspite of prime enzyme in demand and key application in cellulosic energy production, this group of enzymes are suffering with lower enzyme activity and poor functional stability which directly influence the poor bioconversion efficiency of cellulosic biomass and bioenergy production. This is one the crucial issue which blocks the suitable commercial implementation of bioenergy at global scale. Therefore, researches in this particular area accelerate and speed in up to improve the functional stability of this enzymes. Immobilization of cellulolytic enzymes on nanomaterials is emerging as one of the very promising approaches in this area and supposed to have sustainable future towards improving the functional stability of cellulase enzymes via nanostructure based immobilization. Due to unique physicochemical properties and mode of origin nanoform, these nanomaterials can be an effective tool to enhance the catalytic stability of the cellulase enzymes. Therefore, the present reviews explore the possibilities of immobilization of nanomaterials as one of the promising tool to improve cellulosic bioenergy production. Additionally, one of the prime focus of the review is also based on the types, methods and mode of immobilization using different nanomaterials and analyzed the existing advantages and disadvantages of the process. Moreover, the work has also been highlighted the existing limitation and the future suggestion to improve the process applicability. © 2024 Elsevier B.V.